Neuromuscular performance of dollyo chagui: Comparison of subelite and elite taekwondo athletes - Moreira, P. V. S.; Goethel, M. F.; Cardozo, A. C.; Gonçalves, M. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Aiming to compare the execution time, linear and angular speeds, ground reaction force (GRF) and electromyographic (EMG) parameters between taekwondo athletes of two different standards, 8 elite and 8 subelite black belt taekwondo athletes performed eighteen round house kicks, in two randomized height (Head and Chest), with their dominant lower limb, combining maximum impact and speed, in a selective reaction time design. Kinematic were recorded through 3D kinemetry. Timing parameters and EMG cocontraction index were significantly lower in elite group, while peak of linear (toe and knee), angular speeds (knee and hip), and GRF were significantly higher in elite group. We conclude that reaction time, duration and velocity of kick and cocontraction could be useful in selecting top level taekwondo athletes and monitoring their training status.